Fibrous Dysplasia and Ossifying Fibroma - Solving the Diagnostic Dilemma - O.O. Soyele; M.O. Gbotolorun; R.O. Braimah; A.O. Taiwo; A.A. Ibikunle (Nigerian Dental Journal)
Fibrous dysplasia (FD) and Ossifying fibroma (OF) of the jaws belong to a group of lesions called benign fibro-osseous lesions of the craniofacial  skeleton (BFOL). This group of intraosseous disease processes which are comparable in their microscopic features are characterized by hypercellular fibroblastic stroma containing various combinations of bone or cementum-like tissue and other calcified structures. Of these lesions, FD and OF are the most closely related, and although FD is recognized as a harmatomatous lesion and OF a tumour, these lesions are difficult to distinguish both clinically and histologically from each other. This review of current literature aims to highlight emerging features clinically, genetically and histologically that can help in distinguishing these two lesions.